2018
DOI: 10.3389/fevo.2018.00094
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Antarctic Suspension Feeder Abundances and Seafloor Food-Availability, and Modeling Their Change After a Major Glacier Calving

Abstract: Seafloor communities are a critical part of the unique and diverse Antarctic marine life. Processes at the ocean-surface can strongly influence the diversity and abundance of these communities, even when they live at hundreds of meters water depth. However, even though we understand the importance of this link, there are so far no quantitative spatial predictions on how seafloor communities will respond to changing conditions at the ocean surface. Here, we map patterns in abundance of important habitat-forming… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 47 publications
(82 reference statements)
1
8
0
Order By: Relevance
“…This would therefore restrict the bloom to the eastern part of our study zone in these years, where we found significant higher biomass. A similar 50% to 80% increase in SIC (relative to the precalving period) was also observed (Campagne et al, 2015; Jansen et al, 2018) in the Mertz polynya. Interannual variability in SIC has been reported by Fraser et al (2019), where they demonstrated that fast ice regulates the size and the total sea ice production in the Cape Darnley polynya.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This would therefore restrict the bloom to the eastern part of our study zone in these years, where we found significant higher biomass. A similar 50% to 80% increase in SIC (relative to the precalving period) was also observed (Campagne et al, 2015; Jansen et al, 2018) in the Mertz polynya. Interannual variability in SIC has been reported by Fraser et al (2019), where they demonstrated that fast ice regulates the size and the total sea ice production in the Cape Darnley polynya.…”
Section: Discussionsupporting
confidence: 76%
“…Iron is thought to be particularly enriched in the mCDW, as the mCDW comes in contact with the shelf before intruding between 100 and 300 m in the polynya (Moreau et al, 2019; Silvano et al, 2017). Biomass and net community production doubled in the shallow waters (<500 m) over the continental shelf in the eastern part of the polynya after calving (Jansen et al, 2018; Shadwick et al, 2017). Our results follow these previous observations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modeling work indicates widespread suspension feeder cover on the banks (Jansen et al. ), and distinct communities of benthic macroinvertebrates particularly along the steep edges of the banks and the coastal and continental slopes (Jansen et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…Diverse and abundant benthic macrofaunal communities are found along the shelf-break and on the shallower section of the shelf between 200 and 600 m . Modeling work indicates widespread suspension feeder cover on the banks (Jansen et al 2018a), and distinct communities of benthic macroinvertebrates particularly along the steep edges of the banks and the coastal and continental slopes (Jansen et al 2018b). A more detailed descriptive analyses of the fish community inhabiting the George V shelf can be found in Causse et al (2011), and a detailed description of the benthic invertebrate communities in Post et al (2011).…”
Section: Study Areamentioning
confidence: 99%